Nudging as a strategy to prevent behavioural rebound effects in the early phases of design - Mammen, Anna Lodberg; Hartvigsen, Emilie Mia Dirch; Van der Loo, Imke Gerrie Hanne; Pigosso, Daniela Cristina Antelmi (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Despite the recognition that ca. 50% of the potential environmental gains of sustainability-oriented interventions are offset by rebound effects (RE), effective strategies that can prevent the occurrence of rebound effects are currently missing. To address this gap, this paper explores how nudging can be used to prevent RE during the early phases of design of products, product/service-systems and socio-technical systems. Through a Systematic Literature Review, 23 nudges that have the potential to promote sustainable behaviour were identified and subsequently classified into four categories: ‘Decision information’ (e.g. descriptive norms), ‘Decision structure’ (e.g. defaults), ‘Decision assistance’ (e.g. pre-commitment), and ‘Miscellaneous’ (e.g. priming). The identified nudges served as the foundation for the development of a novel design tool that can support the selection of nudges to prevent RE in the early phases of design, with indication of potential additional RE emerging from the implementation of the selected nudges. In addition to the development of the tool, this study mapped existing research gaps that can guide further research in the field.